Triglyceride to high‐density lipoprotein cholesterol ratio variability and incident diabetes: A 7‐year prospective study in a Chinese population. Issue 10 (8th April 2021) - Cai, Zefeng; Chen, Zekai; Fang, Wei; Li, Weijian; Huang, Zegui; Wang, Xianxuan; Chen, Guanzhi; Wu, Weiqiang; Chen, Zhichao; Wu, Shouling; Chen, Youren
Abstract: Aims/Introduction: The correlation between triglyceride to high‐density lipoprotein cholesterol (TG/HDL‐C) ratio variability and incident diabetes has not been fully elucidated. We aimed to characterize the relationship between TG/HDL‐C ratio variability and new‐onset diabetes in Chinese adults. Materials and Methods: A total of 45, 911 patients with three TG and HDL measurements between 2006 and 2011 were enrolled. Average real variability (ARV) were used to evaluate variability, and participants were grouped according to tertiles of TG/HDL‐ARV. Results: There were 3, 724 cases of incident diabetes mellitus during the observation period (6.24 ± 1.2 years). The 7‐year cumulative incidences of diabetes mellitus in tertiles 1, 2 and 3 were 6.13%, 8.09% and 11.77%, respectively. New‐onset diabetes increased with the tertiles of TG/HDL‐ARV. This association was further confirmed after adjustment for mean TG/HDL‐C ratio, TG/HDL‐C ratio change slope, fasting plasma glucose variability (ARV) and other traditional risk factors for diabetes, the hazard ratio value for incident diabetes was 1.38 (1.25–1.50) for the highest tertile, and risk of diabetes increases by 4% with a one standard deviation increase in TG/HDL‐C ratio variability. Restricted cubic splines showed a dose–response relationship between TG/HDL‐C ratio variability and incident diabetes. Similar results were obtained in various subgroup and sensitivity analyses. Conclusions: High TG/HDL‐C variability was associated with a higher risk of diabetes in Chinese adults, independent of the direction of TG/HDL‐C variability. Abstract : High TG/HDL‐C variability was associated with a higher risk of diabetes in a Chinese population and the relationship was independent of the direction of the TG/HDL‐C variations.